Perceived behavioral control as a moderator: scientists' attitude, norms, and willingness to engage the public - Ho, Shirley S. (2023)
Scientists play important roles in conducting public engagement, but evidence shows that scientists perceive great challenges in doing so. Drawing broadly from the theory of planned behavior (TPB), this study examines factors predicting scientists' willingness to conduct public engagement. This study further examines how perceived behavioral control (PBC) of conducting public engagement would moderate the relationships between the proposed predictors and scientists' willingness to conduct public engagement. Using survey data collected from 706 scientists based in Singapore, this study found that attitude toward and personal norms of conducting public engagement, as well as PBC, significantly predicted scientists' willingness to conduct public engagement. Notably, PBC interacted with attitude toward conducting public engagement, the perceived descriptive norms, the perceived positive media influence, and the perceived negative external norms of conducting public engagement, as well as personal norms of conducting public engagement to predict scientists' willingness to conduct public engagement. We postulated the key role that the perception of the ease or difficulty plays in motivating scientists to conduct the skill-intensive endeavor explains the significant moderating effects. The theoretical implications on the TPB and the practical implications for public engagement are further discussed.